2003
DOI: 10.1074/jbc.m308573200
|View full text |Cite
|
Sign up to set email alerts
|

Target of Rapamycin (TOR)-signaling and RAIP Motifs Play Distinct Roles in the Mammalian TOR-dependent Phosphorylation of Initiation Factor 4E-binding Protein 1

Abstract: The translational repressor protein eIF4E-binding protein 1 (4E-BP1, also termed PHAS-I) is regulated by phosphorylation through the rapamycin-sensitive mTOR (mammalian target of rapamycin) pathway. Recent studies have identified two regulatory motifs in 4E-BP1, an mTOR-signaling (TOS) motif in the C terminus of 4E-BP1 and an RAIP motif (named after its sequence) in the N terminus. Other recent work has shown that the protein raptor binds to mTOR and 4E-BP1. We show that raptor binds to full-length 4E-BP1 or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 38 publications
7
115
0
3
Order By: Relevance
“…Our work showing partial reversal of sT-mediated foci formation indicates that the 4E-BP1 phosphorylation site S83 contributes to that MCV sT cell transformation activity. sT transformation is eliminated by a raptor-binding mutant of 4E-BP1 (38)(39)(40), suggesting that mTOR and CDK1 cooperatively promote sT-induced cell transformation. These findings hint at the possibility that this residue is also permissive for cell transformation induced by other oncoproteins that promote mitogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work showing partial reversal of sT-mediated foci formation indicates that the 4E-BP1 phosphorylation site S83 contributes to that MCV sT cell transformation activity. sT transformation is eliminated by a raptor-binding mutant of 4E-BP1 (38)(39)(40), suggesting that mTOR and CDK1 cooperatively promote sT-induced cell transformation. These findings hint at the possibility that this residue is also permissive for cell transformation induced by other oncoproteins that promote mitogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Unlike 4E-BP1.S83A, phosphorylation-defective and raptor-binding mutants (T37A/T46A and I15A/F114A) efficiently inhibited eIF4G binding to eIF4E and in vitro cap-dependent translation (32,(38)(39)(40), suggesting that S83 phosphorylation does not play a significant role in general cap-dependent translation regulation.…”
Section: S83-phosphorylated 4e-bp1 Colocalizes With Centrosomes Duringmentioning
confidence: 99%
“…70 However, strikingly, phosphorylation of this fragment within cells is greatly reduced versus intact 4E-BP1, suggesting that the amino terminal region contains a feature required for normal phosphorylation of 4E-BP1. Further analysis revealed that this involves the four amino-acid motif Arg-Ala-Ile-Pro (RAIP), which is required for phosphorylation of Thr37/46/70 and Ser65 70,71 and appears to mediate a rapamycin-insensitive input from mTOR, which is dependent upon amino acids (especially leucine). A major consequence of this modification is that eIF4E becomes sequestered by D4E-BP1 (Figure 2), leading to decreased levels of eIF4F complexes and inhibition of cap-dependent translation (while IRES-driven translation can continue).…”
Section: E-bp1 Is Subject To Caspase-dependent Cleavage In Apoptoticmentioning
confidence: 99%
“…Akt phosphorylates TSC2, decreasing its Rheb-GAP function (Garami et al, 2003, Inoki et al, 2005a, Inoki et al, 2005b) that results in mTOR activation. mTOR exists in two distinct complexes, one of which contains the adaptor protein Raptor that recruits S6K1/2 and 4E-BP, the two mTOR effectors involved in translation control (Beugnet et al, 2003, Choi et al, 2003, Schalm et al, 2003. The drug rapamycin disrupts mTOR-Raptor interactions, thereby preventing mTOR from phosphorylating S6K1/2 and 4E-BP (Kim et al, 2002, Oshiro et al, 2004.…”
Section: Regulation Of Mtor and Its Effectorsmentioning
confidence: 99%